A combination of hybrid polydopamine-human keratinocyte growth factor nanoparticles and sodium hyaluronate for the efficient prevention of postoperative abdominal adhesion formation. (15th January 2022) - Wei, Guangbing; Wang, Zijun; Liu, Ruilin; Zhou, Cancan; Li, Enmeng; Shen, Tianli; Wang, Xingjie; Wu, Yunhua; Li, Xuqi
Abstract: Postoperative abdominal adhesion (PAA) is one of the more universal complications of abdominal surgery with a frequent incidence. Currently available keratinocyte growth factor (KGF)-based glues for the prevention of adhesions remain a great bottleneck since their long-term biological activity in vivo is insufficient. In this study, we fabricated hybrid polydopamine (PDA)-KGF nanoparticles (PDA-KGF NPs) by using an in situ self-assembly and polymerization method. The physicochemical properties of the PDA-KGF nanoparticles were systematically characterized. The effect of preventing PAA in rats was evaluated by using hybrid PDA-KGF NPs combined with hyaluronate (Ha). The expression levels of inflammatory factors and the degree of inflammatory cell infiltration in the injured peritoneum were evaluated by enzyme-linked immunosorbent assays and hematoxylin-eosin staining, respectively. The levels of phospho-Src expression were revealed by Western blotting. The degree of fibrosis and the density of deposited collagen fibers were measured with real-time reverse-transcription polymerase chain reaction and picrosirius red staining. The results indicated that the PDA-KGF NPs combined with Ha greatly prevented the incidence of abdominal adhesion s and promoted the repair of mesothelial cells in injured peritoneum. More importantly, the PDA-KGF NPs combined with Ha obviously reduced collagen deposition and fibrosis and inhibited the inflammatory response. Our results suggest that PDA-KGF NPs combined with Ha are promising barrier-like biomaterials for the effective prevention of postoperative tissue adhesion. Statement of significance: Postoperative abdominal adhesion (PAA) as an inevitable postoperative complication affected the quality of life of patients. Currently available methods for preventing adhesions mainly employ degradable biomaterials. Previous research demonstrated that a hybrid keratinocyte growth factor (KGF)-sodium hyaluronate (Ha) gel could prevent the formation of PAAs. However, its clinical outcomes are not satisfactory since their bioactivity in vivo is too short. In this article, we fabricated hybrid polydopamine (PDA)-KGF nanoparticles (PDA-KGF NPs), which extend KGF bioactivity, effectively prevent PAA. Moreover, PDA-KGF NPs could remarkably reduce both collagen deposition and fibrosis, inhibit the inflammatory response, and promote mesothelial regeneration. Overall, the PDA-KGF NPs combined with Ha exhibit efficient antiadhesion properties, may provide a promising clinical protocol for the prevention of PAA. Graphical Abstract: Image, graphical abstract